Working conditions, health and lifestyle of workers who work in transport companies, Ñaña, Lurigancho-Chosica, 2018 - Keyla Elizabeth Capcha Díaz (2019)
Objective: to determine the relationship between working and health conditions, and the lifestyleof employees working in three transport companies in Ñaña, Lurigancho-Chosica. Methodology:quantitative approach which was non-experimental, cross-sectional and correlational. The sampleincluded 192 workers selected by non-probabilistic convenience sampling, including criteria forinclusion and exclusion. The data collection instruments were: the “Working and health conditionsquestionnaire”, prepared by Benites et al. (2017) and adapted and validated by Capcha (2018), with aratio of 0.72 with KR - 20, and the “Lifestyle questionnaire”, prepared by Pender (1996), used by Mucha(2014) with an Aiken V value of 1.0 and reliability with Cronbach’s alpha of 0.93. Results: there is arelationship between variables, working and health conditions, and lifestyle, which was found with ap - value of 0.004, according to the Chi - square statistical analysis. Similarly, a relationship was foundbetween the dimensions of lifestyle and working and health conditions, with a p - value <0.05, exceptin the stress management dimension. Conclusion: there is a relationship between the study variables.